اسلامی اقتصادی فکر اور برٹش انڈیا کے مسلمانوں کا جائزہ: An Overview of Islamic economic thought and the Muslims of British India - Awan, Dr. Muhammad Hammad Ul Mustafa; Dr. Hafiz Muhammad Saleem; Waqar Ahmed (Al Manhal Research Journal, 2022)
This article represents an attempt to study and analyse Quaid-e-Azam’s views on economic matters of the Muslims of united India and highlights his role to make the Muslims financially sound and his efforts to safeguard the rights of Muslims under British rule. Moreover this work discusses the famous issue of Waqf-al-Awlad, how the issue emerged and how it was settled in favour of the Muslims by the efforts of Quaid-e-Azam.Quaid’s outlook on the issue of usury and his strong desires and efforts to eradicate usury from the economy of Pakistan have been elaborated at length. In this research analytical method has been adopted, as the issues discussed have historical back ground.The purpose of this research is to make people of Pakistan realize their responsibility to make Pakistan a true Islamic State following the teachings of Quaid-e-Azam. If people of Pakistan act upon the Quaid’s teachings sincerely they may be able to make Pakistan a strong Islamic welfare state in a short period of time.